The story behind an exhibited rag rug : report from a workshop cleaning - Håkanson, Lena (FormAkademisk, 2023)
In my paper, I describe my insights as manager of the textile workshop at the Department of Design at Linnaeus University, as well as how we teach material-based work. Part of my work as a workshop manager is to conduct a major clean-up at the end of every year. Last year, when I was standing in front of a pile of waste textiles, I began to reflect on how this pile of textile had been transformed from well-working material into waste. In a previous project with the research group Praktikforum, together with my colleagues, I explored what kinds of waste we produced when we made material-based artistic work. Thus, it was no surprise that practice-based work produced waste. The surprise was what I could understand from it. Looking closer into the waste, I obtained a deeper understanding of what had happened in the workshop during the year; how the students had used the material, what they had learned and what sometimes went wrong became obvious. I gained a deeper understanding of how we use, understand and teach/learn about materials and how we can develop the workshop by learning from the waste. At the same time, I learned the technique of ‘inbraiding’. For me, this was a new craft technique, in which waste textiles can be used when making rugs. I saw the opportunity to use the waste and upcycle it. By exhibiting the rug, I want to discuss the possibility of working more sustainably with crafts.